Scavenger Species‐typical Alteration to Bone: Using Bite Mark Dimensions to Identify Scavengers. Issue 6 (7th August 2015) - Young, Alexandria; Stillman, Richard; Smith, Martin J.; Korstjens, Amanda H.
Abstract: Scavenger‐induced alteration to bone occurs while scavengers access soft tissue and during the scattering and re‐scavenging of skeletal remains. Using bite mark, dimensional data to assist in the more accurate identification of a scavenger can improve interpretations of trauma and enhance search and recovery methods. This study analyzed bite marks produced on both dry and fresh surface deposited remains by wild and captive red fox ( Vulpes vulpes ) and Eurasian badger ( Meles meles ), as well as domestic dog ( Canis familiaris ). The bite marks produced by foxes were distinguishable from those made by badgers and dogs based on ranges of mean length and breadth of pits. The dimensional data of bite marks produced by badgers and dogs were less discernible. Bone modifications vary due to a variety of factors which must be considered, such as scavenger species‐typical scavenging behavior, scavenger species' dentition, condition and deposition of remains, and environmental factors.